Safety and efficacy of a feed additive consisting of iron chelate of ethylenediamine for all animal species (Zinpro Animal Nutrition (Europe), Inc.). (28th April 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of iron chelate of ethylenediamine (Iron‐EDA‐Cl) as a feed additive for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) identified several issues related to the data provided concerning the chemical characteristics of the additive. Based on the information provided, the FEEDAP Panel considered unlikely that the additive consists only of iron monochelate of EDA, but of several coexisting (iron) species; therefore, in the absence of adequate experimental data and owing to the uncertainties identified, the Panel cannot conclude on its identity and characterisation. The FEEDAP Panel concludes that the additive is safe for poultry for fattening and reared for laying/breeding, but cannot conclude on the safety for other animal species/categories. The FEEDAP Panel cannot conclude on the safety of the additive for the consumer or the environment. The FEEDAP Panel concludes that handling the additive poses a risk to users by inhalation. The additive should be considered as non‐irritant for the skin but irritant for the eyes and skin sensitiser. The FEEDAP Panel cannot conclude on the efficacy of the additive.